Cost-Effectiveness Analysis of the Oncotype DX Breast Recurrence Score® Test from a US Societal Perspective - Berdunov V; Cuyun Carter G; Laws E; Luo R; Russell CA; Campbell S; Abdou Y; Force J (Dove Medical Press, 2024)
Vladislav Berdunov,1 Gebra Cuyun Carter,2 Ewan Laws,1 Roger Luo,2 Christy A Russell,2 Sara Campbell,2 Yara Abdou,3 Jeremy Force4 1Putnam, London, UK; 2Exact Sciences, Madison, WI, USA; 3School of Medicine, UNC, Chapel Hill, NC, USA; 4School of Medicine, Duke University, Durham, NC, USACorrespondence: Vladislav Berdunov, Putnam, 22-24 Torrington Place, Fitzrovia, London, WC1E 7HJ, UK, Tel +44 7542947557, Email vlad.berdunov@putassoc.comBackground and Objectives: The 21-gene assay (the Oncotype DX Breast Recurrence Score® test) estimates the 10-year risk of distant recurrence in hormone receptor positive (HR+) and human epidermal growth factor receptor 2 negative (HER2-) early-stage breast cancer to inform adjuvant chemotherapy decisions. The cost-effectiveness of the 21-gene assay compared against standard clinical-pathological risk tools alone for HR+/HER2- early-stage breast cancer was assessed using an economic model informed by evidence from randomized controlled trials.Materials and Methods: A cost-effectiveness model consisted of a decision-tree to stratify patients according to their Recurrence Score (RS) results and the use of adjuvant chemotherapy, followed by a Markov component to estimate the long-term costs and outcomes of the chosen treatment. Distributions of patients and distant recurrence probabilities were derived from the TAILORx (N0) and RxPONDER (N1) trials. The model was evaluated from a healthcare payer and societal perspective. Endocrine therapy and chemotherapy use were informed using clinical expert opinion to reflect US clinical practice and were combined with Medicare drug costs (2021) to estimate the cost of treatment. Societal costs included lost productivity and patient out-of-pocket costs obtained from literature.Results: The Oncotype DX test generated more quality-adjusted life-years (QALYs) (N0: 0.25; N1: 0.08) at a lower cost (N0: -$13,395; N1: -$2526) compared to clinical-pathological risk alone from a societal cost perspective. The overall conclusions from the model did not change when considering a payer perspective. The main cost drivers were avoidance of distant recurrence for N0 (-$12,578), and the cost of adjuvant chemotherapy for N1 (-$2133). Lost productivity had a major impact in the societal perspective analysis (N0: -$4607; N1: -$1586).Conclusion: Adjuvant chemotherapy decisions based on the RS result led to more life year gains and lower healthcare costs (dominant) compared to using clinical-pathological risk factors alone among patients with HR+/HER2- N0 and N1 early-stage breast cancer.Keywords: cost-effectiveness, tumour profiling test, breast cancer, chemotherapy, the Oncotype DX test